REGULAR SUB-SEQUENTIALLY DENSE INJECTIVE IN THE CATEGORY OF S-POSETS - Haddadi, M.; Moghaddasi, Gh. (Italian Journal of Pure and Applied Mathematics, 2014)
Sequentially dense monomorphisms were first introduced and studied by Giuli for projection algebras and followed by Ebrahimi, Mahmoudi, Moghaddasi and Shahbaz for S-acts. In this paper we use the notion of sub-Cauchy sequences and introduce the class of regular sub-sequentially dense monomorphisms for S-posets, denoted by \(M\)s. We investigate the properties of the class \(M\)s and study \(M\)s-injectivity of S-posets. Further, we find \(M\)s-injective hull of S-posets over some kind of semigroups.